Pengaruh Layanan Konseling Kelompok Dengan Pendekatan Cognitive Behavioral Therapy Kepada Gen Z Terhadap Perilaku Berpacaran - Asiah Asiah; Theresia Gultom (Jurnal Tematik, 2025)
This study aims to determine the Effect of Group Counseling Services with a Cognitive Behavioral Therapy Approach to Gen Z on Dating Behavior. The method used in this study is a quantitative method. This type of research is Quasi Experimental using One Group Design Pre-Test and Post-Test. The subjects in this study were 6 students of grade X who had high dating behavior scores. The instrument used was a dating behavior scale. The instrument was given before and after the implementation of group counseling services. Data were analyzed using the Wilcoxon test to see whether there was a significant effect of providing group counseling services with a cognitive behavioral therapy approach on dating behavior in students. The results of the analysis showed that the initial results (pre-test) in the experimental group obtained an average of 173.33 while the post-test data obtained an average of 95.66. The results of the hypothesis analysis show that the Wilcoxon rank test obtained Jhitung = 3 while Jtabel = 0. Jhitung > Jtabel where 3 > 0, from this calculation it can be seen that the treatment in the experimental group means that the hypothesis that states there is a significant influence of providing group counseling services using the cognitive behavioral therapy approach on dating behavior in gen z can be accepted. The conclusion of the study is that there is a significant influence of providing group counseling services through the cognitive behavioral therapy approach on dating behavior.